Gilbert Omenn and his syndrome - Ahmad Al Aboud; Khalid Al Aboud (Our Dermatology Online, 2012)
Gilbert Omenn is a well-known American Geneticist. In the 1965, He reported a rare genetic disorder -later known as Omenn syndrome. This syndrome is a variant of severe combined immunodeficiency which is associated with hypereosinophilia. It is one of the differential diagnoses of neonatal erythroderma.This concise report sheds light on Gilbert Omenn and the syndrome that bears his name.